The suppression of Ganoderma boninense on oil palm under mixed planting with taro plants - SUWANDI SUWANDI; MONICA ALESIA; RUDI PUTRA MUNANDAR; RAHMAD FADLI; SUPARMAN SUPARMAN; CHANDRA IRSAN; A. MUSLIM (Society for Indonesian Biodiversity, 2024)
Abstract. Suwandi S, Alesia M, Munandar RP, Fadli R, Suparman S, Irsan C, Muslim A. 2024. The suppression of Ganoderma boninense on oil palm under mixed planting with taro plants. Biodiversitas 25: 1143-1150. Basal stem rot, caused by Ganoderma boninense, is highly destructive in monoculture oil palm plantations. This study evaluated Ganoderma boninense infections and oil palm growth in mixed plantings of oil palm seedlings and taro plants (Japanese, Bogor, and Indralaya taro). Ganoderma, colonizing rubber wood blocks, was inoculated into mixed plants, and the infection was compared to single-inoculated oil palm and taro plants. The interference of mixed planting with taro plants on the growth of oil palm seedlings was compared between inoculated and noninoculated mixed and single planting. Ganoderma inoculation caused simultaneous disease (dual-host infection) in mixed oil palm and taro plants. Ganoderma infection was less severe in taro plants compared to oil palm, whether in single or mixed planting. Over six months, oil palm root necrosis and disease index were reduced by 82% to 96% and 65% to 71%, respectively, while no significant effect was observed at nine months. The decay of Ganoderma-colonized wood improved by 44.1% to 84.0% in mixed planting, with no significant impact on mycelium viability. Taro plants did not inhibit oil palm growth, including plant height, leaf area, and relative growth rate of primary root length, in both the presence and the absence of Ganoderma infection. This study highlights the potential of mixed planting with taro to reduce Ganoderma disease in oil palm.